Polymer-induced swelling of solid-supported lipid membranes - Kreuzer, Martin; Trapp, Marcus; Dahint, Reiner; Steitz, Roland (Membranes, 2016)
In this paper, we study the interaction of charged polymers with solid-supported 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) membranes by in-situ neutron reflectivity. We observe an enormous swelling of the oligolamellar lipid bilayer stacks after incubation in solutions of poly(allylamine hydrochloride) (PAH) in D2O.